PRELIMINARY STUDIES ON THE OESTROGENIC ACTIVITY OF GUINEA GRASS (PANICUM MAXIMUM) VAR. S112 AND STYLO (STYLOSANTHES GRACILIS) - ADEPOJU, AMOS; ADEGBOLA , A. A.; AYININUOLA, S. I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Purified oestrogenic extracts were obtained from 25g samples of gound air dried leaf and stem portions of guinea grass (Panicum maximum var. S112) and stylo 0.05ml of each of these extracts was injected into immature female mice weighing 8 to 10g in order to determine the oestrogenic activities of the forages at different stages of growth. The mean values obtained for the oestrogenic potency of guinea grass were 0.30, 0.23, 1.41 and 0.86mcg of diethyl stilbestrol per kg of the leaf portion and 0.28, 0.15, 1.01 and 0.49mcg of diethyl stilbestrol per kg of the stem portion at early vegetative, full vegetative, early bloom and full bloom growth stages respectively. Mean values for stylo leaf portion were 0.62, 0.85, 1.50 and 0.75mcg of diethyl stibestrol per kg, and those for the stem portion were 0.43, 0.62, 0.80 and 0.55mcg of diethyl stilbestrol per kg at the early vegetative, full vegetative, early bloom and full bloom growth stages, respectively. The results indicated that the oestrogenic content of stylosanthes gracilis was significantly higher (P. .05) in the leaf than in the stem, and the differences observed during the various stages of growth were significant.